Pembelajaran Bahasa Arab Di Ma'had Abu Bakar As Shiddiq Universitas Muhammadiyah Surakarta Tahun Ajaran 2016/2017 - Saleh, Muhamad Roslan, Dr. M. Abdul Kholiq Hasan, M.A., M.Ed, Dr. Syamsul Hidayat, M.Ag (2017)
Learning Arabic has the concept of teaching by a very significant position to reach the goal. Arabic Education Program in Ma'had Abu Bakar As-Siddiq specializes in the study of Arabic and teaching, has the challenge to produce output that has both cognitive and psychomotor competencies, so it is ready to take part in various educational institutions both formal and non-formal primarily related with Arabic and teaching materials, and as one of the indicators of professional competence that must be possessed by students reflected in competence in Arabic. This research is classified as descriptive qualitative research. The research approach used is qualitative descriptive study. The research location is memilihan locations in Ma'had Abu Bakar As Siddiq Muhammadiyah University of Surakarta. The reasons for selecting this place because it is a boarding school that uses a high-level education as an introduction to learning the Arabic language. When the study was conducted over three months of the month of April 2016 to June 2016. Methods of data collection in this research was conducted through observation, interview and documentation. Analysis of the data in this study using a qualitative descriptive analysis consists of three activities which are at the same data collection data reduction, data presentation and conclusion or verification. Based on the results of research on learning Arabic in Ma'had Abu Bakar As Siddiq Universitas Muhammadiyah Surakarta in 2016/2017 can be concluded that the learning materials are provided in learning in ma'had Ma'had Abu Bakar As Siddiq not only the material aspects of language , but coupled with the materials of Islamic studies. Arabic language learning strategies in this Ma'had include: learning Arabic language elements (Aswat, mufradat, tarakib) language skills and learning strategies (istima', Kalam, qira'ah, kitabah). Evaluation of learning is done on a regular basis, to immerse themselves in the learning material. Obstacles in Teaching Arabic in Ma'had Abu Bakar As Siddiq Universitas Muhammadiyah Surakarta Doctrine year 2016/2017 is Arabic as a second language for students, instructional media used is still lacking and Infrastructures inadequate. Solutions in Learning Arabic in Ma'had Abu Bakar As Siddiq Universitas Muhammadiyah Surakarta Doctrine year 2016/2017 is to add infrastructure needs in the learning of Arabic as well as provide variety in learning Arabic as well as holding a variety of skills to be dominated cleric in learning, to boredom learners, so that is always enthusiastic, diligent and full participation.